Response: Whose Table for “The Retarded”? - O'brien, John (Journal of religion, disability & health, 2005)
They key role of those treated as outsiders in building community is identified. The importance of appreciating people with intellectual disabilities as possessing affirmative gifts and the necessity of understanding “outsiders” through sharing life is asserted. The centrality of dependency in understanding community building and the positive historical role of the principle of normalization in highlighting the negative effects of segregation and control are discussed.